EFFECT OF OMEPRAZOLE IN THE TREATMENT OF PEPTIC ULCER AND COMPARISON WITH FAMOTIDINE - Serap ARSLAN; Tankut KÖSEOĞLU; Ergün KARAAĞAOĞLU; Yusuf BAYRAKTAR; Burhan KAYHAN; Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-